River flood risk quantification using reliability index method’s safety factor (Level I) and first order second moment (Level II), a case study of Plumbon River, Semarang city, Central Java - Nugroho, Eka Oktariyanto; Suryadi, Yadi; Andrean, Renaldy; Soekarno, Indratmo; Syabhan, Kiromi (Edelweiss Applied Science and Technology, 2024)
This paper presents a case study on flood risk assessment using reliability as the analysis system’s framework. The objectives of this study are to describe a flood event condition through quantitative analysis of how a river acts as the reliable hydraulic resistance and serves as an improvement from past studies’ calculations to study flood resistances for rivers using sections’ factual shapes. The study refers to the Performance Indices Ten, Safety Factor (SF) or Level I, which uses the exceedance probability as the performance index, and First Order Second Moment (FOSM) or Level II, which uses the probability for failure as the performance index that assumes all probability densities to be convertible to Gaussian distributions. Study in Plumbon River is analyzed with two methods: (a) Analyzing the river as a whole single unit to produce a single quantification; (b) Analyzing the river as separated units based on stream locations (upstream & downstream) classified by its slope level, and scored based on its rank compared to the other units. The results show that: (a) Level I and II results in similar trend and particular defined numbers for reliability; (b) River classification analyzes each section better, showing slope level is directly proportional to reliability; and (c) Trapezium-shaped assumption is not suitable for river with complex morphology.